Wettability of a microgrid‐structured polymer film with microfabrication utilizing the stick–slip phenomenon. Issue 30 (10th April 2017) - Naito, Keishi; Yamada, Taisei; Tsutsumi, Takafumi; Yashiro, Kisaragi
ABSTRACT: A microgrid structure was formed on the surface of a polyethylene terephthalate (PET) film with an original microfabrication method (termed SS processing) utilizing the stick–slip (SS) phenomenon, and the effect of this surface structure on wettability was evaluated. Microgrid‐structured films could be fabricated by two‐axis SS processing. Moreover, an arbitrary parallelogram microgrid structure could be formed by selecting the direction of the second SS processing with respect to that of the first SS processing. Both water contact angle and water sliding angle of the SS‐processed film were larger than that of the PET film. Hence, the SS‐processed film showed a petal‐like effect. Furthermore, the water sliding angle of the microgrid‐structured film showed anisotropy due to the pinning effect derived from the microgrid structure. As a result, it is revealed that a hydrophobic PET film with a petal‐like effect and anisotropic wettability can be fabricated by SS processing. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45140. Abstract :